An introduction to clinical emergency medicine - Swaminatha V. Mahadevan (Cambridge University Press, 2005)
Now with updated ACLS algorithms An Introduction to Clinical Emergency Medicine is a much-needed resource for individuals practicing in this challenging field. It takes a novel approach, describing in detail the best and most current methods including initial patient evaluation, generation of differential diagnoses, problem-solving and management of challenging conditions based on presenting symptoms. Unlike other textbooks, in which the diagnosis is known, this textbook approaches clinical problems as clinicians approach patients - without full knowledge of the final diagnosis. It provides an understanding of how to approach patients with undifferentiated conditions, ask the right questions, gather historical data, utilize physical examination skills and order and interpret laboratory and radiographic tests. It provides current management and disposition strategies with controversies presented, including pearls and summary points for each topic covered. The book is multi-author, each contributor chosen because of a track record in teaching as well as being internationally recognised experts in the specialty